2013
DOI: 10.3171/2012.11.jns12689
|View full text |Cite|
|
Sign up to set email alerts
|

A single center's experience with the bedside subdural evacuating port system: a useful alternative to traditional methods for chronic subdural hematoma evacuation

Abstract: Object The traditional methods for managing symptomatic chronic subdural hematoma (SDH) include evacuation via a bur hole or craniotomy, both with or without drain placement. Because chronic SDH frequently occurs in elderly patients with multiple comorbidities, the bedside approach afforded by the subdural evacuating port system (SEPS) is an attractive alternative method that is performed under local anesthesia and conscious sedation. The goal of this study was to evaluate the radiographic and clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
0
30
1
Order By: Relevance
“…However, surgical treatment can result in improvement of cognitive ability in a short-term (1-month follow-up), and improvement of neurological status in a longterm (1-year follow-up), despite some patients will remain dependent with limited mRS scores. This is in contrast to past research [25,26], but more recent studies have shown the similar results to our findings [15,16].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, surgical treatment can result in improvement of cognitive ability in a short-term (1-month follow-up), and improvement of neurological status in a longterm (1-year follow-up), despite some patients will remain dependent with limited mRS scores. This is in contrast to past research [25,26], but more recent studies have shown the similar results to our findings [15,16].…”
Section: Discussioncontrasting
confidence: 57%
“…The term "chronic" subdural hematoma has been loosely defined, with various authors applying it to those in the different stage of CSDH. According to CT scan, hematoma density is known to decrease with time, passing from a high-stage to an iso-and finally a low density stage [15,16]. Therefore, lower hematoma densities are expected to be seen in the late stage of hematoma course.…”
Section: Discussionmentioning
confidence: 99%
“…Safain et al found a mean volume reduction of 68.2% for SEPS and 76.2% for traditional techniques (p = 0.25), 14 and Rughani et al found a mean reduction in maximal CSDH thickness of 45.4% in the BHC group and 40.5% in the SEPS group (p = 0.31);…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14,17 Two considered outcomes based on the maximum CSDH width, while the other 2 studies considered volume estimates. Overall, radiological improvement was seen in 150 of 197 collections (76.1%), and these and other studies commented on the lack of correlation between radiological and clinical outcomes with many patients experiencing symptomatic improvement despite lack of radiological improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Twist drill craniostomy appears to have morbidity similar to that of BHD, with complications reported in 0-18% of patients with twist drill procedures [9,10,11] vs. 0-25% for BHD [12,13]. Yet the rates of recurrence are empirically higher with bedside procedures: 25.9% with SEPS vs. 14.8% with BHD in the study of Rughani et al [14]; 18% (twist drill) vs. 8% (BHD) requiring reoperation/drainage in the study of Horn et al [9]; and, similarly, 17% (twist drill) vs. 0% (BHD and craniotomy) rates of inadequate SDH drainage in the study of Safain et al [15]. Many of these differences are not reported as statistically significant, but this is possibly due to the low power of the studies.…”
Section: Introductionmentioning
confidence: 90%